Hierarchy in twentieth-century Sefwi (Ghana) - Boni, S; Boni, Stefano (1999)
﻿ The dissertation aims to provide an understanding of the relation between political-economic power and the attribution of social value in twentieth-century Sefwi (Ghana). The existing literature on relations of dominance amongst the Akan has flaws: works examine single relations of dominance in isolation; studies focus mostly on discontinuity and change; peripheral areas are neglected. In the dissertation these issues are addressed. Hierarchy is used as an analytical tool which enables one to link diverse expressions of dominance; the persistence of certain hierarchical patterns throughout the twentieth century is analysed alongside transformations; and the focus is on Sefwi, a marginal region of the Akan world. The dissertation is divided into five sections. The introduction presents the methodological and theoretical approach adopted in the work. Part one is concerned with change in hierarchical patterns: twentieth-century dynamics are analysed to determine the extent of change with reference to chiefly power, capitalist.relations and gender issues. Part two shows that unequal relations inform three hierarchical domains -ancestry, gender and seniority. Part three addresses the issue of the coherence and unity of hierarchy by examining modes of organization of experience that cut across the three domains of inequality: reference is made to the use of kinship terms; concepts of ownership, caretakership and help; recourse to the supernatural; food and drink transactions. In the conclusion, Sefwi hierarchy is examined in a wider comparative and theoretical perspective with reference to the notions of 'encompassing of the contrary' (Dumont) and 'fetishization' (Marx).